Effect of Moringa oleifera leaf powder supplementation on weight gain of toddler in the working area of Naibonat health center, Kupang regency - Jessica Allo; Sidarta Sagita; Rahel Rara Woda; Christina Olly Lada (World Nutrition Journal, 2020)
Introduction: Undernutrition prevalence in East Nusa Tenggara is very high. One of the intervention to overcome this problem is by providing foods enriched with vitamins and minerals. One of the plant that contains great amount of vitamins and minerals is Moringa which thrives in almost all of the mainland of Timor. This study aims to determine whether there is an effect of Moringa leaf powder supplementation on weight gain of children under five years of age at the working area of Naibonat Health Center in Kupang Regency.Methods: Experimental study with pre-test post-test control group design was conducted among children aged 2-5 years in the working area of the Naibonat Health Center in Kupang Regency. The study was conducted with consecutive sampling technique with a total subjects of 50 children consisting of 25 children in the treatment group and 25 children in the control group. The intervention group was given 25 grams of Moringa leaf powder for 14 days. Results: There was a significant increase in body weight of the treatment group after supplementation of 25 grams of Moringa leaf powder for 14 days (p< =0.,001). In the control group, there was no significant difference of body weight after the study.Conclusions: Moringa oleifera leaf powder supplementation of 5-10 grams has been able to increase body weight by 0.53 kg on children under five years of age at the working area of Naibonat Health Center in Kupang Regency by increasing the child's appetite.